Technology and clientelist politics in India - Steven I. Wilkinson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper argues that new computer, smartphone, and universal ID technologies are reducing the incentives for political clientelism in the delivery of social programmes in India, especially by allowing party leaders to bypass local brokers to credit-claim for better service delivery and allowing politicians to deliver programmatic service delivery much more efficiently than in the past, with fewer diversions. Politicians are responding to these changed incentives, not surprisingly, by investing more money in large social programmes, supporting technological efforts to improve their efficiency, and increasing campaign expenditures to advertise these improvements and link them to party leaders at the expense of local brokers who used to monopolize these local party- voter linkages.
Keywords: D72; O32; O33; O38; 330; clientelism; India; technologies; social programmes; service delivery